Fasciotomy for Deep Posterior Compartment Syndrome in the Lower Leg: A Prospective Study. (May 2016) - Winkes, Michiel B.; van Zantvoort, Aniek P.M.; de Bruijn, Johan A.; Smeets, Stef J.M.; van der Cruijsen-Raaijmakers, Marike; Hoogeveen, Adwin R.; Scheltinga, Marc R.
Background: Patients with exercise-induced lower leg pain may suffer from deep posterior chronic exertional compartment syndrome (dp-CECS). Current evidence for the efficacy of surgery is based on retrospective studies. Effects of fasciotomy on symptoms associated with dp-CECS have not been systematically studied, and reasons for unsuccessful surgery are unknown. Purpose: To report the short- and long-term effects of fasciotomy on pain, tightness, and cramps in a prospective cohort of patients with isolated dp-CECS. Study Design: Case series; Level of evidence, 4. Methods: Between September 2011 and January 2015, pain, tightness, cramps, muscle weakness, and diminished sensation were scored (5-item verbal rating scale ranging from very severe [5 points] to absent [1 point]) in patients with dp-CECS before and after fasciotomy. Outcomes were graded as excellent, good, moderate, fair, or poor. Fair and poor cases were again analyzed during a follow-up visit in the outpatient department. Results: Forty-four patients underwent surgery for isolated dp-CECS. Short-term follow-up (median, 4 months; range, 3-7 months) was complete in 42 of the 44 patients (95%; median patient age, 23 years; 23 male; 64 operated legs). Long-term follow-up (median, 27 months; range, 12-42 months) was complete in 34 of 37 eligible patients (92%). Before surgery, exertional pain was very severe (27%) or severe (61%). Fasciotomy improved all symptoms, both in the short term (preoperative vs postoperative pain, 4.1 ± 0.6 vs 2.3 ± 1.1; P < .001) and the long term (pain, 4.2 ± 0.6 vs 2.7 ± 1.3; P < .001). Levels of tightness, cramps, muscle weakness, and diminished sensation demonstrated similar significant improvements. Short- and long-term symptom scores did not differ. The short-term outcome was excellent in 29%, good in 29%, moderate in 21%, fair in 12%, and poor in 10% of patients. In the long term, outcomes were similar (excellent, 12%; good, 35%; moderate, 24%; fair, 18%; and poor, 12%). An unsatisfactory outcome (fair or poor) was often caused by alternative types of CECS (eg, anterior or lateral CECS) or to medial tibial stress syndrome. Based on their outcome, 76% of patients would opt for surgery again. Conclusion: Fasciotomy was beneficial in 71% of patients with dp-CECS in the lower leg; 47% of study patients experienced a good to excellent outcome. Outcomes were stable in the long term. Persistent complaints were often caused by other untreated conditions.